Retraction notice to "Fungal diversity is negatively affected by habitat fragmentation: a meta-analysis" [Current Opinion in Microbiology 37 (2017) 61-66]. (June 2017) - Grilli, G; Longo, S; Huais, PY; Pereyra, M; Verga, E; Urcelay, C; Galetto, L
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal ). This article that has already been published in <Current Opinion in Microbiology, 37, June 2017 61-66>, http://dx.doi.org/10.1016/j.mib.2017.03.015 has been withdrawn at the request of the editor and publisher. The publisher regrets that an error occurred which led to the premature publication of this paper. This error bears no reflection on the article or its authors. The publisher apologizes to the authors and the readers for this unfortunate error.